Role of tertiary structures on the Root effect in fish hemoglobins - Ronda L.; Bettati S.; Verde C.; Balsamo A.; Mazzarella L.; Mozzarelli A.; MERLINO, ANTONELLO; VERGARA, ALESSANDRO (Biochimica et Biophysica Acta (BBA) - Proteins and Proteomics, 2013)
Many fish hemoglobins exhibit a marked dependence of oxygen affinity and cooperativity on proton concentration, called Root effect. Both tertiary and quaternary effects have been evoked to explain the allosteric regulation brought about by protons in fish hemoglobins. However, no general rules have emerged so far. We carried out a complementary crystallographic and microspectroscopic characterization of ligand binding to crystals of deoxy-hemoglobin from the Antarctic fish Trematomus bernacchii (HbTb) at pH 6.2 and pH 8.4. At low pH ligation has negligible structural effects, correlating with low affinity and absence of cooperativity in oxygen binding. At high pH, ligation causes significant changes at the tertiary structural level, while preserving structural markers of the T state. These changes mainly consist in a marked displacement of the position of the switch region CD corner towards an R-like position. The functional data on T-state crystals validate the relevance of the crystallographic observations, revealing that, differently from mammalian Hbs, in HbTb a significant degree of cooperativity in oxygen binding is due to tertiary conformational changes, in the absence of the T–R quaternary transition.